ANALYSIS OF FACTORS AFFECTING THE USE OF CASHLESS MOBILE PAYMENT IN MILLENIAL GENERATIONS OF BATAM CITY - Yandi Suprapto (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
The purpose of this study is to determine the factors or influences that lead to the use of cashless mobile payments on the Batam millennial generation. The number of electronic-based payment media provided is expected to be able to create payment transactions that are practical, efficient, safe and encourage the creation of a Less Cash Society (LCS). When compared to Indonesia with other ASEAN countries, the level of use of electronic-based payments in the community is still low. Generation Y or the Millennial generation (15 to 39 years) in 2017 showed a figure of 40.29% or as many as 105,520,300 individuals from 261,890,900 Indonesians considered to have the potential to increase the use of electronic-based payments and encourage public awareness of LCS. The intention to use cashless mobile payments is the dependent variable. Attitudes, behavioral beliefs, financial costs, security and social influence act as independent variables for this study. Determination of the research object was carried out by purposive sampling method, namely the millennial generation (15 to 39 years) in Batam. Research data collection is based on the questionnaire method, namely electronic and online questionnaires with 230 collected data. The research data were analyzed through multiple regression analysis using SSPSS. The results obtained indicate that the variables of attitude, security and social influence have a significant positive effect on the intention to use cashless mobile payment, while the variables of behavioral beliefs and financial costs do not have a significant effect on the intention to use cashless mobile payments.